The low-temperature magnetostructure and magnetic field response of Pr0.9Ca0.1MnO3: the roles of Pr spins and magnetic phase separation. (6th January 2016) - Tikkanen, J; Geilhufe, M; Frontzek, M; Hergert, W; Ernst, A; Paturi, P; Udby, L
Abstract: With the goal of elucidating the background of photoinduced ferromagnetism phenomena observed in the perovskite structured (Pr, Ca) manganites, the low-temperature magnetostructure of the material was revised using cold neutron powder diffraction, SQUID magnetometry and ab initio calculations. Particular emphasis was placed on determining the presence of nanoscale magnetic phase separation. Previously published results of a canted A-AFM average ground state were reproduced to a good precision both experimentally and theoretically, and complemented by investigating the effects of an applied magnetic field of 2.7 T on the magnetostructure. Explicit evidence of nanoscale magnetic clusters in the material was obtained based on high-resolution neutron diffractograms. Along with several supporting arguments, we present this finding as a justification for extending the nanoscale magnetic phase separation model of manganites to the material under discussion despite its very low Ca doping level in the context of the model. In the light of the new data, we also conclude that the low temperature magnetic moment of Pr must be ca. 300% larger than previously thought in this material, close to the high spin value of per formula unit.